The formation of autophagosomes during lysosomal defect: A new source of cytotoxicity - Button, Robert W. (Autophagy, 2017)
Macroautophagy/autophagy comprises autophagosome synthesis and lysosomal degradation. It is well known that lysosomal defects cause toxicity to cells. However, it has not been investigated previously if cytotoxicity is conferred by autophagosome formation during lysosomal defect. Recently, we found that the formation of autophagosomes in such conditions also causes cytotoxicity, in addition to lysosomal defect insults. We revealed that a partial reduction in autophagosome synthesis was beneficial for cell survival in cells bearing the autophagosome formation-based toxicity. Our study suggests that production/accumulation of autophagosomes during lysosomal defect directly induces cellular toxicity, and this process may be implicated in the pathological conditions where lysosomes are defective.